The benefits of an integrated liaison psychiatry and dermatology service for complex dermatology Patients—a case series. Issue 4 (5th October 2022) - Roberts, Victoria; Chan, Jonathan; Davies, Jo; Angus, Janet
Abstract: Psychodermatology is a specialist area which refers to the assessment and treatment of the psychosocial aspects of dermatology. This includes the management of patients with primary psychiatric disorders, psychosocial co‐morbidities of existing skin disease or psychological distress caused by their skin conditions. We report the benefits and cost savings of a recent pilot of an integrated service of a consultant dermatologist and a liaison psychiatrist providing coordinated care to complex psychodermatology patients. Abstract : Psychodermatology refers to the management of psychosocial aspects of dermatology. We report the benefits and cost savings of an integrated service of a dermatologist and a liaison psychiatrist providing coordinated care to complex patients.